1987
DOI: 10.1099/00221287-133-12-3427
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-dehydrogenase-mediated Solute Transport and ATP Synthesis in Acinetobacter calcoaceticus

Abstract: Evidence is presented that in Acinetobacter calcoaceticus oxidation of glucose to gluconate by the periplasmic quinoprotein glucose dehydrogenase (EC 1 . 1 .99.17) leads to energy conservation.Membrane vesicles prepared from cells grown in carbon-limited chemostat culture exhibited (1) a high rate of glucose-dependent oxygen consumption and gluconate production, (2) glucosemediated cytochrome reduction, (3) uncoupler sensitive, glucose-dependent generation of a membrane potential and (4) glucose-driven accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Studies on the generation of a proton motive force (Ap) by electron transfer in membrane vesicles of E. coli have shown that a significant decrease of Ap requires drastic inhibition of electron transfer (24). With D-lactate as the electron donor, the Ap remained essentially constant when the oxidation rate was inhibited up to 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the generation of a proton motive force (Ap) by electron transfer in membrane vesicles of E. coli have shown that a significant decrease of Ap requires drastic inhibition of electron transfer (24). With D-lactate as the electron donor, the Ap remained essentially constant when the oxidation rate was inhibited up to 60%.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria and mitochondrial membranes of bovine heart (Smith, 1967) and N. crussu (Weiss et al, 1970), plasma membranes of E. coli strain B (Matsushita et al, 1987) and G. oxidans (van Schie et al, 1987), as well as complex I and the peripheral part of the complex both of N. crassa were prepared as described. The respiratory activities of isolated bovine heart and N. crussa mitochondria and plasma membranes from G. oxiduns were measured in a Clarke-type oxygen electrode (Weiss et al, 1970;Strohdeicher et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…The aerobic respiratory chain of E. coli is relatively simple, with respect to its components and its sequence, and has a number of primary dehydrogenases coupled to the respiratory chain, including flavoproteins such as D-lactate, succinate, and NADH dehydrogenases (13) and the quinoprotein GDH (25). The E. coli aerobic respiratory chain is also branched at the end with cytochrome o and cytochrome d as terminal oxidases.…”
mentioning
confidence: 99%
“…1), implying that GDH is rate limiting in the D-glucose oxidation. van Schie et al (25) showed that D-glucose oxidation generated A4i in E. coli membrane vesicles by using a tetraphenylphosphonium-electrode. Generation of A* was confirmed here by fluorescence quenching of diS-C3-(5) in RSO membrane vesicles of E. coli GR19N (Fig.…”
mentioning
confidence: 99%